Symptomatic fractures in systemic sclerosis: A case–control study. Issue 1 (February 2023) - Sampaio-Barros, Marília M; Bortoluzzo, Adriana B; da Silva, Henrique Carriço; Luppino-Assad, Ana Paula; Pereira, Rosa Maria R; Sampaio-Barros, Percival D
This case–control study analyzed risk factors for symptomatic fractures in a group of 52 patients with systemic sclerosis compared with a group of 104 patients without fractures, matched for sex and age, who were attended at a single systemic sclerosis outpatient clinic from 2010 to 2020. Fractures affected predominantly vertebral (65.4%), rib (13.5%), and hip (7.7%) joints, while the mean age of fracture was 55.3 ± 9.5 years. Age at disease onset, age at diagnosis, disease duration, age at menarche, and age at menopause were similar in both groups, and 58.9% of the patients were menopausal at the time of the fracture. The presence of fractures had a significant association with densitometric osteoporosis (p < 0.001), lower weight (p = 0.032), and bone mineral index (p = 0.044), anti-RNA polymerase III (p = 0.040), use of corticosteroids (p = 0.019), and bisphosphonates (p < 0.001), as well as with densitometric T-scores of lumbar spine (p < 0.001), femoral neck (p = 0.025), and total hip (p = 0.013). Multivariate analysis showed that the variables significantly associated with fractures were high doses of corticosteroids (odds ratio = 4.10; 95% confidence interval = 1.290–13.090; p = 0.017), bisphosphonates (odds ratio = 3.91; 95% confidence interval = 1.699–8.984; p = 0.001), negative anti-Scl70 (OR = 0.34; 95% confidence interval = 0.124–0.943; p = 0.038), and lumbar T-score (odds ratio = 0.39; 95% confidence interval = 0.034–0.460; p = 0.010). In conclusion, symptomatic fractures were associated predominantly with lower bone mineral density of lumbar spine and use of high doses of corticosteroids and bisphosphonates in this cohort.